"Raced" Organizations and the Academic Success of Underrepresented Minority Faculty Members in Sociology. Issue 2 (April 2019) - Spalter-Roth, Roberta; Shin, Jean H.; Smith, Jason A.; Kalb, Amber C.; Moore, Kyle K.; Cid-Martinez, Ismael; Toney, Jermaine
The purpose of this research is to determine whether participating in "raced" organizations benefits underrepresented minority (URM) faculty members in their quest for tenure and promotion to associate professor of sociology. Raced organizations such as historically black colleges and universities began as segregated institutions because black students and faculty members were prevented from attending or working at white-dominated institutions. Over time, raced organizations developed within the white-dominated institutions and were often created in opposition to white or "mainstream" sociology. Latina/o organizations (including Hispanic-serving institutions) started years after organizations for black scholars and have followed a similar pattern and purpose. Although historically white institutions no longer legally segregate URM organizations and activities, these organizations and activities often remain marginalized and devalued. The authors examine the relationship of participating in such organizations in contrast to publishing in peer-reviewed journals for climbing the academic ladder at research-extensive and other institutions. The authors find that there is a significant relationship between publishing and being promoted. URM faculty members must follow the "publish or perish" model, following historically white male norms for an "ideal" career in the academic world. The work of black and Latina/o sociologists still appears to be marginalized. Only one type of raced organization or activity, belonging to a URM-oriented section of the American Sociological Association, is significantly related to upward mobility at either research-extensive or non-research-extensive institutions. The authors conclude with a series of policy recommendations for increasing the academic status and well-being of URM faculty members.